Telling the Collective Story: Symbolic Interactionism in Narrative Research - van den Hoonaard, Deborah K. (Qualitative Sociology Review, 2013)
Recent years have seen tremendous growth of interest in narrative approaches to research in both the social sciences and the humanities. Much of this research focuses on the stories of individuals and how they tell them. This article addresses the contribution of a symbolic interactionist approach to develop the “collective story” (Richardson 1990) through the use of sensitizing concepts. It focuses on research on the experience of widows, widowers, and Iranian Bahá’í refugees to Canada to demonstrate how one can use sensitizing concepts to craft a collective story of members of marginalized populations that sit at the bottom of the “hierarchy of credibility” (Becker 1967).